Multivariable Analysis of Patients With Severe Persistent Postprocedural Hypotension After Carotid Artery Stenting. (December 2019) - Oshin, Olufemi; Varcoe, Ramon; Wong, Jackie; Burrows, Sally; Altaf, Nishath; Schlaich, Markus; Weerasooriya, Rukshen; Gray, William; Deloose, Koen; Baumgartner, Iris; Mwipatayi, Bibombe P.
Purpose: To assess the incidence and predictors of severe, persistent postprocedural hypotension (PPH) after carotid artery stenting (CAS).Materials and Methods: A total of 146 patients (mean age 72.8 years; 104 men) who underwent 160 CAS procedures using a standardized protocol at 3 vascular centers were retrospectively analyzed. The primary endpoint was postprocedural hypotension, defined as a reduction in systolic blood pressure (SBP) >40 mm Hg from baseline or an SBP of <90 mm Hg sustained for >1 hour after CAS. Potential prognostic factors for postprocedural hypotension were identified and subjected to logistic regression analyses; outcomes are presented as the odds ratios (ORs) with 95% confidence intervals (CIs).Results: PPH developed in 36 (24.7%) patients after 37 (23.1%) CAS procedures. These patients had significantly longer intensive care unit and hospital stays than those who did not develop hypotension (p<0.001). PPH was associated with severe lesion calcification (OR 6.28, 95% CI 1.81 to 21.98, p=0.004) and contrast volume (OR 1.02, 95% CI 1.01 to 1.02, p<0.001). A 4-fold increase in the risk of PPH (OR 4.22, 95% CI 1.38 to 13.33, p=0.012) was found between the embolic protection device most associated with PPH (Angioguard) and the device least associated with PPH (Emboshield NAV6). A similar trend was also observed for the Precise vs Xact stents (OR 6, 95% CI 2.08 to 17.6, p=0.001). Bootstrapped multivariable modeling identified the Precise stent and contrast volume as significant predictors of persistent postprocedural hypotension. Further investigation of the contrast volume revealed associations with sex, severe calcification, arch type, previous coronary artery bypass surgery, and primary stenting, suggesting that the contrast volume reflects the complexity of the procedure.Conclusion: The complexity of the procedure and type of stent may play a role in the development of postprocedural hypotension after CAS.